Polycyclic Aromatic Hydrocarbons and digestive tract cancers - a perspective - Diggs, Deacqunita L. (2011)
Cancers of the colon are most common in the Western world. In majority of these cases, there is no familial history and sporadic gene damage seems to play an important role in the development of tumors in the colon. Studies have shown that environmental factors, especially diet, play an important role in susceptibility to GI tract cancers. Consequently, environmental chemicals that contaminate food or diet during its preparation becomes important in the development of GI cancers. Polycyclic aromatic hydrocarbons (PAHs) are one such family of ubiquitous environmental toxicants. These pollutants enter the human body through consumption of contaminated food, drinking water, inhalation of cigarette smoke, automobile exhausts, and contaminated air from occupational settings. Among these pathways, dietary intake of PAHs constitutes a major source of exposure in humans. Although many reviews and books on PAHs and their ability to cause toxicity and breast or lung cancer have been published, aspects on contribution of diet, smoking and other factors towards development of digestive tract cancers and strategies to assess risk from exposure to PAHs have received much less attention. This review, therefore, focuses on dietary intake of PAHs in humans, animal models, and cell cultures used for GI cancer studies along with epidemiological findings. Bioavailability and biotransformation processes, which influence the disposition of PAHs in body and the underlying causative mechanisms of GI cancers, are also discussed. The existing data gaps and scope for future studies is also emphasized. This information is expected to stimulate research on mechanisms of sporadic GI cancers caused by exposure to environmental carcinogens.